Asterix and the Magic Carpet - Uderzo, Albert (UK, 2002)
Cacofonix's tuneless singing always makes it rain - which is just what they want in Rajah Watzit's distant Eastern kingdom. The guru Hoodunnit has threathened to end a terrible drought by sacrificing lovely princess Orinjade. Can the Gauls, flown in on the fakir Watziznehm's magic carpet, rescue her? The bard's finest hour has come!...
Keywords: Graphic; Juvenile Fiction